Analysis of drilling and reaming technique of large diameter high directional hole and gas extraction effect - Weifeng YANG; Jianlin LIU; Fei LIU; Jianguo ZHAO; Zhiwei CHU (Meikuang Anquan, 2024)
Aiming at the problems of low comprehensive efficiency and high treatment cost in the conventional treatment of mining pressure relief gas in “U” ventilation mining face, taking a mining face in Jincheng Mining Area, Shanxi Province as the research object, ϕ200 mm large diameter high-position directional borehole for gas control of mining pressure relief is proposed. Based on the analysis of the technical difficulty of large-diameter high-position directional borehole in the roof of the coal mine, the key drilling equipment are selected, including ZDY20000LD directional drilling rig, BLY460 mud pump truck and multi-power expanding drilling tool. The combined strong slag-discharge directional drilling technology and multi-dynamic single-reaming technology have been developed to realize directional drilling of ϕ120 mm high hole and single-reaming of ϕ200 mm hole under complex formation conditions, the comprehensive drilling efficiency is more than 50% higher than that of conventional multi-stage expanding. The gas drainage effect shows that the area of 30-40 m away from the roof and 40 m away from the return air roadway is the mining fracture intensive development area. The average gas drainage concentration in the borehole is maintained at more than 40% and the maximum pure amount of gas drainage is 10.94 m3/min, which has remarkable effect.